(untitled) (Security Dialogues, 2025)
There is no doubt that conflicts (violent or non-violent) are an integral part of the relations between different actors at both, the national, regional and international levels. Starting from this conclusion, there is an inevitable need for applying appropriate strategies and approaches that will enable their efficient and successful management and resolution. It is exactly from such aspect that the significance of the negotiation process arises as an instrument for peaceful resolution of open issues or disputes, through the establishment and realization of communication between the opposing parties. However, as the experience to date in this regard shows, the realization of the negotiation process is not always established and realized in accordance with the projected visions. Hence, the focus of this paper is specifically directed towards the analysis of the negotiation process essence, mainly through the prism of some of the existing theoretical and practical aspects in this regard. Specifically, by analyzing the characteristics of the basic elements, phases and models of the negotiation process, the aim is closer identification of the main challenges and perspectives related to the applicability of the negotiation process.